(untitled) - Carmoy, Hervé de (Cambridge, Massachusetts, 1990)
The book examines the rise and fall of banks around the world. The world of international banking has entered a period of profound crisis. The market is being transformed as the US banking environment becomes increasingly fragile and nine out of the top ten banks are now Japanese. The book analyzes the constraints facing the world's largest banks, and the strategic choices
Keywords: Banks and banking,Banks and banking,Banks and banking,Banks and banking,Competition, international,Strategic planning; Europe,Japan,United states